Efficient Anthocyanin Extraction from Aqueous Mixture of Cocoa Peel Using Microwave Assisted Extraction (MAE) Method - Lutsi, Nurtsulutsiyah; Yakub Hendrikson Manurung; Istiqomah Rahmawati (Journal of Biobased Chemicals, 2023)
Anthocyanins are polyphenolic compounds whose existence is very abundant in nature with diversity in various types of plants. The purpose of this study was to optimize the anthocyanin extraction process from cocoa shell waste using the MAE method in order to obtain the optimum particle size, ingredient/solvent ratio, and extraction time to produce high anthocyanin concentrations. The optimized extraction process variables include the size of the particle (1,05; 1,25; 1,49 and 2,5 x 10-4 m), the ratio of substrate/solvent (4,5; 12,5; 62,5; 79,5 x 10-3 g/mL), time of extraction (2, 4, 10, 14 minutes) and microwave power (100; 275; 450; 625 watts). The Design Expert vs11 program with the Box-Behnken Design Response Surface Methodology (RSM) was used in the research and the selection of process conditions was carried out from a combination of factors that resulted in an optimal response. The relationship between variables on the modeled anthocyanin concentration response: Y=0,000486-9,98637E-07A+0,026734B0,000041C-7,58240E-07D-0,000102AB+2,48606E-07AC+2,62878E09AD-0,000539BC+0,000012BD+9,71853E08CD (A: particle size; B: cocoa shell: solvent ratio; C: extraction time; D: microwave power). The optimal response value for anthocyanin concentration was 11,85.10-4 M and the conditions of the extraction process are the particle size in the extraction process was 0,105 mm, the ratio of cocoa peel mass/ethanol was 0,03125 g/mL, the extraction time was 2 minutes, and the microwave power was 100 W.